Optimization and Experimental Analysis of Electroless Nickel Plating on the Diamond Surface - Qingming Fan; Guokang Su; Congmin Zhu; Hui Qi; Pengfan Li; Xiumei Shen; Chuanyun Zhang; Kai Cheng (Micromachines)
Coating diamond particle surfaces with a layer of high-temperature resistant nickel, which possesses weldability, effectively enhances the bonding strength between diamond particles and substrates in pre-grinding tools. This improves their stability and strength at high temperatures, thereby enhancing the performance, lifespan, and efficiency of grinding tools. This paper explores the electroless nickel plating process on diamond surfaces, analyzes the working principle of electroless nickel plating on diamond surfaces, and proposes the use of 2 g/L AgNO3 solution and 2 g/L AgNO3 + 10 mL/L NH3·H2O solution as Pd-free activating solutions. Experimental studies have demonstrated the feasibility of using silver nitrate as an activator, and it has been found that the 2 g/L AgNO3 + 10 mL/L NH3·H2O solution achieves a higher surface plating ratio when used as an activator for electroless nickel plating on diamond surfaces. Based on this, through orthogonal and single-factor experimental methods, the effects of ammonia solution concentration, sodium hypophosphite concentration, plating temperature, and diamond particle size on electroless nickel plating on diamond surfaces were investigated. The optimal process for electroless nickel plating on diamond surfaces was obtained: ammonia solution concentration of 17.5 mL/L, sodium hypophosphite concentration of 33 g/L, and plating temperature of 80 °C. Under this process, using diamond particles with a size of 120/140 for electroless nickel plating, a surface plating ratio of 10.75% electroless nickel-plated diamond can be achieved.